Community project for happiness : academic community engagement - Edward, Oswald Timothy (Faculty of Business & Management, 2021)
Community Projects for Happiness provides personal reflection of academic service based on academics-students experience in reviewing and contributing to community engagements and services. The articles were written based on approved projects under Projects for Happiness, a community initiative sponsored by the non-profit organization Khind Starfish Foundation, to assist marginalised communities and the underprivileged. The foundation has allocated some grants as a sponsorship for "Projects for Happiness" to assist underprivileged communities, through planning and implementation of innovative community activities by university and college students in Malaysia. The nature of these activities focuses on six themes: education, helping underprivileged communities, cultural & arts, environmental protection, animal welfare and racial harmony. Community Projects for Happiness provides an overview and guidance for designing and implementing community-academics programs through the active involvement of students and communities. The principles, steps, and indicators are primarily meant to guide program designs, including the development of requests for proposals, the implementation of program activities, and the development of performance management plans and evaluations. Community Projects for Happiness also provides basic information for those who are interested to know more about key considerations when engaging communities in educational projects.